INVENTARISASI HASIL TANGKAPAN IKAN YANG DIDARATKAN OLEH KELOMPOK PENANGKAPAN CCDP-IFAD DI PAYUM KELURAHAN SAMKAI KABUPATEN MERAUKE - Natalis Wagemu; Norce Mote; Sendy L. Merly (Musamus Fisheries and Marine Journal, 2018)
Coastal Community Development International Fund for Agricultural Development (CCD-IFAD) or called the Coastal Community Development Project (PMP) is a collaboration of the Ministry of Maritime Affairs and Fisheries (KKP) with CCDP – IFAD. CCDP - IFAD position in Merauke regency greatly helps the economic income of coastal communities. This study aims to determine the types of fish caught and landed by the CCDP-IFAD group in Payum. The method used is survey. The results obtained 13 types of landed fish including: Lates calcaliver, Johnius macropterus, Pennahia macrocephalus, Eleutheronema tetradactylum, Thryssa spp., Lebtobrama mulleri, Cynoglossus heterolepis, Plototus canus, Rhinoprenes pentanemus, Mugil cephalus, Arius spp., Triusurus savala, Dasyatis spp . Keywords: CCDP-IFAD; Fish; Coastal.